Spectroscopic investigation on a XVII-XVIII century terracotta slab from Calabria, Southern Italy. Issue 1 (1st April 2022) - Caridi, F.; Acri, G.; Paladini, G.; Venuti, V.; Crupi, V.; Faenza, P.; Majolino, D.
Abstract: In this paper the elemental composition of a XVII-XVIII century terracotta slab, preserved in the Gerhard Rohlfs Museum of the Calabrian Greek Language of Bova, Reggio Calabria, Southern Italy, was investigated through the X-Ray Fluorescence (XRF) spectroscopic technique. The investigation allowed us to detect elements closely related to the manufacture of the slab. In addition, Principal Component Analysis (PCA) statistical method was applied to experimental data in order to recognize the provenance of the artefact through a comparison with local clay materials collected from historical buildings of Bova.